• 5

Решение.

 Сохраним обозначения, введенные при решении пре­дыдущей задачи. Мы имеем (см. рис. 56, 57)

AK=jb, Ai = ±(a + d), KL = AL-Ak=j(a — b-\-d), АМ=~а, AN = j(b + d), Ш=АМ —AM=±-(—a + b+d). Следовательно,

<АВг + CD1)—(AD* + ВС2) = [а2 + (d—b)I)—[b2 + (d—a)2] =

= 2ad— 2bd = 2d (a—b) = 2AC-DB\

2(KL2-MN2) = 2 [(gZ^H?y_(-« + » + *yj = 2ad—2bd =

= 2d (a — b) = 2AC-DB.

Остается применить формулу (45).

Авторы: 1379 А Б В Г Д Е З И Й К Л М Н О П Р С Т У Ф Х Ц Ч Ш Щ Э Ю Я

Книги: 1908 А Б В Г Д Е З И Й К Л М Н О П Р С Т У Ф Х Ц Ч Ш Щ Э Ю Я